Puddling and its Impact on Physio-Chemical Characteristics of Soil - Devi, Ayekpam Dollina; Singh, Teekam; Kumari, Megha (Chronicle of Bioresource Management, 2020)
Crop management is essential for optimizing agricultural productivity, conserving water resources, and ensuring sustainable farming practices. In context to rice, puddling is an important crop management practice since time immemorial. It provides benefits such as weed control, reduced water percolation, and easier transplanting. However, it disturbs the soil structure and affects the properties of soil, over time, these changes degrade soil fertility and soil health. Slow root development for successive crops like wheat and pulses due to plough pan formation is a serious problem for farmers. However, from production point of view, puddling in rice dominates over unpuddled field. Although it is advantageous in rice production, the negative long-term impact of puddling calls for sustainable alternatives, such as reduced tillage and direct seeding to maintain soil health while ensuring high yields.